If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(n + -1) = 16 Reorder the terms: -2(-1 + n) = 16 (-1 * -2 + n * -2) = 16 (2 + -2n) = 16 Solving 2 + -2n = 16 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -2n = 16 + -2 Combine like terms: 2 + -2 = 0 0 + -2n = 16 + -2 -2n = 16 + -2 Combine like terms: 16 + -2 = 14 -2n = 14 Divide each side by '-2'. n = -7 Simplifying n = -7
| -5(p+4)=0 | | -5-b=-2 | | 5n+4-3n=16 | | -5(r-3)=25 | | -2-5b=28 | | 4x+5=6x-3x | | -x^2+10x+y-21=0 | | -n+5=12 | | -5(k+2)=-30 | | 2x-3f= | | 4-5(3x+2)-12=27 | | -2(r-2)=-10 | | 8x-7=3x+28 | | -4(k+5)=-44 | | 3x-6=x+2 | | 4ac+6a= | | 4+2x=22 | | 40(2-3)=36n | | -4(4+m)=-4 | | -5(-1+p)=55 | | 12w+11=5w-(-4+w) | | 13-8x=85-22x | | X^2+36x+324=12 | | 5(-2+p)=-55 | | 2x+40=180 | | 122-5x=3x+15 | | -2(-1+x)=0 | | 16+3t=17-t | | 62x-3x=7x+22 | | 3(4+x)=-3 | | Q^3-125=0 | | -3+4m=37 |